Nonparametric Recursive Kernel Type Eestimators for the Moment Generating Function Under Censored Data - Bouzebda, Salim; Elhattab, Issam; Slaoui, Yousri Slaoui; Taachouche, NourElhouda (Statistics, Optimization & Information Computing, 2023)
We are mainly concerned with kernel-type estimators for the moment-generating function in the present paper. More precisely, we establish the central limit theorem with the characterization of the bias and the variance for the nonparametric recursive kernel-type estimators for the moment-generating function under some mild conditions in the censored data setting. Finally, we investigate the methodology’s performance for small samples through a short simulation study.